Diversi Pidana Anak dalam Perspektif Hukum Pidana Islam; Implementasi dan Faktor Efektivitas - Indra Naposo Harahap; Fauziah Lubis (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to examine the implementation of diversion in handling juvenile criminal cases from the perspective of Islamic criminal law and to analyze the factors affecting the effectiveness of diversion. This article is categorized as qualitative library research. The methodology used is normative legal research with a statutory approach and content analysis. The results indicate that juvenile diversion aligns with the principles of Islamic criminal law, which emphasize rehabilitation, forgiveness, and reconciliation as educational and restorative resolution efforts. Although the diversion mechanism is regulated in the Juvenile Criminal Justice System Law, its implementation is still hindered by limited understanding among law enforcement officers, inadequate facilities, and low public awareness. Therefore, the integration of national law and Islamic values is crucial for diversion to function effectively, provide optimal protection, and reflect substantive justice and the welfare of children.